Discovery of delayed gas production after implantation of a continuous-flow left ventricular assist device and a preliminary exploration of the mechanisms of its occurrence - Lv, Pengfei; Zhang, Yadong; Ma, Hongbin; Wang, Fenghua; Chen, Ailin; Zhang, Zhixiang; Wang, Fan; Liu, Tianwen; Zhang, Jiemin; Liu, Xiaocheng; Liu, Zhigang (Frontiers in Cardiovascular Medicine, 2024)
OBJECTIVE: To characterize the gas production phenomenon in the animal model of left ventricular assist device (LVAD), and study its mechanism.METHODS: An in vitro bubble precipitation experiment was conducted, and the blood samples of Parma spp. animals were divided into ordinary group and oxygen-enriched group according to whether they were oxygenated or not at the time of blood collection, and a static control group was set up respectively. Blood gases were drawn and analyzed before and after the experiment. Activate the pump, and the number of air bubbles in the loop was measured by ultrasound at different rotational speeds; CFD was applied to simulate the flow field in the blood pump, and pressure, fluid velocity vector and shear force diagrams were plotted, and a thrombus model was constructed and the flow field was simulated and plotted as a cloud diagram.RESULTS: There was a statistical difference in the number of bubbles in the inflow and outflow tubes of the blood pump (P values of 0.04 and 0.023, respectively), and the number of bubbles in the outflow tubes of both groups was significantly higher than the number of bubbles in the inflow tubes. The number of bubbles in the tubes of both the oxygen-enriched and normal groups was significantly higher than that in the inflow group. In both the normal and oxygen-enriched groups, more gas was produced at higher speeds than at lower speeds.Blood gas analysis showed that the reduced gas composition in the blood was mainly oxygen.Flow field simulation results: the high rotation speed group had lower central pressure and greater scalar shear. The thrombus simulation group was more prone to turbulence, sudden pressure changes, and greater shear than the normal group.CONCLUSION: Blood gas production is associated with higher partial pressures of blood oxygen, higher rotation speed, and intrapump thrombosis, and the mechanism of pump gas production is degassing of dissolved gases rather than cavitation of water, and the gas released is most likely to have oxygen. The degassing phenomenon is an warning factor for pump thrombosis.